AUTOMATED WATER MANAGEMENT SYSTEM FOR AGRICULTURE CROP (International Journal of Food and Nutritional Sciences, 2023)
The Automated Water Management System for Agriculture Crop aims to optimize water usage in agriculture by integrating modern technologies such as sensors, IoT, and data analytics. This system is designed to monitor soil moisture levels, weather conditions, and crop water needs in real-time, providing automated irrigation solutions that enhance crop yield, reduce water waste, and minimize manual intervention. The implementation of such systems addresses the critical challenges of water scarcity and sustainable farming practices. This study explores the various components of automated water management systems, their applications, benefits, challenges, and potential future developments. The findings highlight the significant role these systems can play in transforming agriculture by making it more efficient and environmentally friendly